InterNet: Detection of Active Abdominal Arterial Bleeding Using Emergency Digital Subtraction Angiography Imaging With Two-Stage Deep Learning - Min, Xiangde; Feng, Zhaoyan; Gao, Junfeng; Chen, Shu; Zhang, Peipei; Fu, Tianyu; Shen, Hong; Wang, Nan (Frontiers in Medicine, 2022)
Objective: Active abdominal arterial bleeding is an emergency medical condition. Herein, we present our use of this two-stage InterNet model for detection of active abdominal arterial bleeding using emergency DSA imaging. Methods: Firstly, 450 patients who underwent abdominal DSA procedures were randomly selecte for development of the region localisation stage (RLS). Secondly, 160 consecutive patients with active abdominal arterial bleeding were included for development of the bleeding site detection stage (BSDS) and InterNet (cascade network of RLS and BSDS). Another 50 patients that ruled out active abdominal arterial bleeding were used as negative samples to evaluate InterNet performance. We evaluated the mode’s efficacy using the precision-recall (PR) curve. The classification performance of a doctor with and without InterNet was evaluated using a receiver operating characteristic (ROC) curve analysis. Results: The AP, precision, and recall of the RLS were 0·99, 0·95, and 0·99 in the validation dataset, respectively. Our InterNet reached a recall of 0·7, the precision for detection of bleeding sites was 53% in the evaluation set. The AUCs of doctors with and without InterNet were 0·803 and 0·759, respectively. In addition, the doctor with InterNet assistant could significantly reduce the elapsed time for the interpretation of each DSA sequence from 84·88 to 43·78 seconds. Conclusions: Our InterNet system could assist interventional radiologists in identifying bleeding foci quickly and may improve the workflow of the DSA operation to a more real-time procedure.